Murmuring the judges - Jardine, Quintin, 1945- (Headline, 1999)
In Edinburgh's old Parliament House, an armed robbery trial is about to take a macabre turn. While the lawyers tussle over the evidence, the judge suddenly collapses in agony - the victim of an apparent heart attack. For Deputy Chief Constable Bob Skinner, with his life finally back on track after the near-collapse of his marriage, the last thing he needs is to be faced with the most baffling case of his career. But as the wave of brutal robberies continues, it emerges that Lord Archergait's death may have been murder - and he's not the only judge whose life is in danger. With a gang of ruthless killers still at large, it's down to Skinner to piece together a puzzle of sinister complexity.